Clinical Case Reports: From Clinical to Science - Ribeiro Junior, Howard Lopes (Brazilian Journal of Case Reports, 2025)
Clinical Case Reports: From Clinical to Science compiles 53 exceptional case reports originally published in the Brazilian Journal of Case Reports during the 2023–2024 biennium. This volume highlights the dynamic interplay between clinical practice and scientific investigation, demonstrating how individual patient experiences can inspire new perspectives in healthcare and foster translational research. The selected cases encompass rare oncological entities, infectious diseases with global implications, unusual anatomical variations, complex surgical challenges, and unexpected therapeutic outcomes. Beyond their immediate clinical relevance, these reports illustrate the critical role of case studies in bridging bedside observations with biomedical science. Each chapter represents not only a clinical narrative but also a story of discovery, perseverance, and innovation. By documenting unique diagnostic and therapeutic challenges, this collection reinforces the value of case reports as a cornerstone of medical literature and a catalyst for scientific advancement. Clinical Case Reports: From Clinical to Science thus serves as both a reference and an inspiration for healthcare professionals, researchers, and students, reaffirming the inseparable bond between clinical practice and scientific progress. ISBN 978-65-981870-2-6 (PDF)